2017
DOI: 10.11604/pamj.2017.28.205.12135
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous subserosal venous rupture overlying a uterine leiomyoma in a young woman

Abstract: Uterine leiomyomas are very common tumors found in women. Rupture of veins on the surface of uterine leiomyoma is an unusual source of hemoperitoneum. It is an extremely uncommon gynaecological cause of hemoperitoneum. It is a life threatening emergency. We report a case of massive intraperitoneal hemorrhage due to rupture of vessels on the surface of subserous leiomyoma. A differential diagnosis of rupture of leiomyoma’ssurface vessel should be considered, while dealing with a case of hemoperitoneum with pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The current case is of a premenopausal patient of low parity (1P), with a positive history of uterine myoma, without any predisposing and precipitating factors. Jenayah et al mentioned that myomas >10 cm have an increased risk for subserosal variceal development (6). In our case the maximum size of the tumor was 9.5 cm, close below the limit.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The current case is of a premenopausal patient of low parity (1P), with a positive history of uterine myoma, without any predisposing and precipitating factors. Jenayah et al mentioned that myomas >10 cm have an increased risk for subserosal variceal development (6). In our case the maximum size of the tumor was 9.5 cm, close below the limit.…”
Section: Discussionsupporting
confidence: 50%
“…Performing an Embase, Scopus, and PubMed search, the number of reported cases was identified at approximately less than 100, including those occurring during pregnancy. Saidi et al reported 50 cases before 1961 (3), Akahira et al reported 7 cases between 1961 and 1997 (4), Jain et al reported no more than 7 cases from 1994 to 2004 (5), and 9 cases were revealed by the search of the present authors between 2005 and 2020 (2,(6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation